2023
DOI: 10.1101/2023.04.01.535040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Avoiding false discoveries: Revisiting an Alzheimer’s disease snRNA-Seq dataset

Abstract: Arising From: Mathys, H. et al. Nature (2019). https://doi.org/10.1038/s41586–019–1195–2 Mathys et al., conducted the first single-nucleus RNA-Seq study (snRNA–Seq) of Alzheimer′s disease (AD). The authors profiled the transcriptomes of approximately 80,000 cells from the prefrontal cortex, collected from 48 individuals – 24 of which presented with varying degrees of AD pathology. With bulk RNA-Seq, changes in gene expression across cell types can be lost, potentially masking the differentially expressed genes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One potential concern is that multiplex, single-cell CRISPR screens that treat cells as pseudo-replicates have the potential to suffer from an overestimation of differentially expressed genes due to the statistical dependency between cells originating from the same starting population 39 . Our singleton validation results allay this concern, but we cannot fully rule out overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…One potential concern is that multiplex, single-cell CRISPR screens that treat cells as pseudo-replicates have the potential to suffer from an overestimation of differentially expressed genes due to the statistical dependency between cells originating from the same starting population 39 . Our singleton validation results allay this concern, but we cannot fully rule out overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Like Grubman et al, they found upregulation of protein folding genes, molecular chaperone genes, and global stress response genes in multiple cell types in late-stage AD samples vs early-stage AD samples. Importantly, it is worth noting that a recent preprint reanalyzed this data set using best-practice approaches and found different results ( Murphy et al, 2023 ), underscoring the importance of re-assessing datasets based on consistently-evolving platforms.…”
Section: Studies In Post-mortem Brain Tissuementioning
confidence: 99%